The Influence Of Training And Work Motivation On Employee Peformance In The Cutting Departement At Adis Dimension Footwear Tangerang Regency - Roji, Fahmi; Yulandari, Sri; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine: (1) the partial effect of training on employee performance; (2) the partial effect of motivation on employee performance; (3) the simultaneous effect of work satisfaction and motivation on employee performance.This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all employees in the Cutting department at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 80 respondents. This study used a saturated sampling technique due to the small population size; therefore, the sample in this study used the entire population of 80 employees as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis using SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, training significantly influences the performance of employees in the Cutting department at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (3.503>1.991) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work motivation significantly influences the performance of Cutting employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (2.602>1.991) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, training and work motivation significantly influence the performance of Cutting employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (27.006>3.12) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that the variables of training and work motivation, both partially and simultaneously, have a significant influence on the performance of Cutting employees at PT. Adis Dimension Footwear Balaraja-Tangerang.